Reflections on the Environmental Impact Assessment Processes in Turkey (European Journal of Multidisciplinary Studies, 2017)
Environmental Impact Assessment (EIA) process is a procedure that the environmental impacts of decisions on people, fauna and flora, soil, weather, climate, land, cultural heritage, etc. are taken into account before the decisions are made. Moreover, the EIA process has gradually been evolved to cover social aspects. However, Turkish legislation and implementation of EIA process seem to have significant problems when it comes to assessment of decisions on social aspects. This article will offer a critical account on the EIA process in Turkey with regard to the analysis of social impacts. The study will especially focus on whether the EIA reports in Turkey deal with the medium and long-term social impacts of the decisions in real terms and whether these reports have practical benefits in decision making processes. Moreover, the author will specifically ask whether EIA reports in Turkey assess the investments in terms of usefulness and sustainability. The main argument in this study is that those significant merits of the EIA process directly depend on the strength, efficiency and applicability of democratic participation mechanisms.